Understanding and using financial data : - Wright, Charles R. (John Wiley & Sons, Inc., 1997)
Designed to walk attorneys through the myriad of items found in corporate annual reports, balance sheets and financial statements which is critical for litigation purposes and for client edification regarding the importance of deciphering financial language in legal documents. Features extensive material on where to find the information you need, how to compare it to the information provided by other companies in the same industry or geographic location, how to corroborate the data in the basic statements, and locating the primary internal documents upon which financial statements are based. This edition contains updated information on the financial reporting consequences of litigation, nonprofit organizations, business interruption insurance, and an appendix with U.S. GAAP pronouncements.